Inactivation of individual cells by divers ions at different LET values - Lokajicek, M V; Cechak, T; Judas, L; Kluson, J; Kundrat, V; Prokes, K (Physica medica, 2001)
A new formula linking the shape of survival curve to the inactivation probabilities after different numbers of cell hits has been derived. It has been used in analyzing recent experimental data obtained with monolayer cells irradiated at definite values of LET (in different parts of Bragg peaks). The new approach allows not only deriving the values of inactivation probabilities at given LET values; unexpected consequences seem to follow especially for inactivation characteristics of carbon ions in different parts of the Bragg peak, too.
Keywords: Animals; biologické modely; protony; Cells; lidé; Cell Nucleus; Models, Biological; Mice; kůže; myši; buněčné jádro; Linear Energy Transfer; lineární přenos energie; Skin; ionty; Protons; Ions; Cell Survival; zvířata; viabilita buněk; buňky; Carbon; uhlík; vztah dávky záření a odpovědi; Dose-Response Relationship, Radiation; Humans